Burdens for Businesses Due to the War in Ukraine - Michael Grömling; Hubertus Bardt (Wirtschaftsdienst)
Abstract The war in Ukraine is placing considerable burdens on the German economy. Based on the economic survey conducted by the German Economic Institute, the different various transmission paths and effects can be assessed. Almost 80% of companies currently see themselves burdened by high energy prices. More than 40% of businesses expect their operations to be impacted in the short term by failed input deliveries; the expected burden due to impending bottlenecks in the energy supply is just as high. Concerns have increased since the first survey in the first half of March. In the medium term, companies expect to face increasing burdens from the war.